Nucléon Electromagnetic Form Factors in a constituent-quark model - Demetriou, P.; Boffi, S.; Radici, M.; Wagenbrunn, R. F. (HNPS Advances in Nuclear Physics, 2019)
The electromagnetic form factors of the nucléon are calculated in an extended chiral constituent-quark model where the effective interaction is described by the exchange of pseudoscalar and vector mesons belonging to the pseudoscalar and pseudovector octet, respectively, and a scalar meson . Two-body current-density operators, constructed consistently with the extended model Hamiltonian in order to preserve gauge invariance and current conservation, are found to give a significant contribution to the nucléon magnetic form factors and improve the estimates of the nucleon magnetic moments.